The efficacy of Philippine native fishes as predators of mosquito larvae under laboratory conditions - Abila, Rochelle G.; Daliong, Emerlyn C.; Keith, Charis Vina E. (2012)
Biological control methods are given much research focus for dengue vector control and for other mosquito-borne diseases as an alternative to chemical-based control due to the emerging threat of strong resistance to pesticides and harmful effects not only to the non-target population but to the environment as well. Larvivorous fish as a biological control agent have been used in mosquito control and many species were proven effective. Among these species are Gambusia affinis, Poecilia reculta, and Oreochromis species. However, these species are introduced species which are aggressive and ecologically invasive that imperil ecosystem balance and biodiversity. This paper studied the efficacy of Philippine native fishes which are Clarias macrocephalus(paltat) and Channa striate(bulig) as predators of mosquito larvae as an alternative to introduced species to eliminate negative impacts connected to their use. Their efficacy in varying temperatures was studied by introducing 10 mosquito larvae in each of the fish container, noting the number of larvae consumed with in 24 hrs. and comparing their consumption to G. affinis. Result showed that C. macrocephalus had the greatest average number of larvae consumed during the feeding experiment followed by the control species, Gambusia affinis and C.striata. Statistically, the date showed that C. macrocephalus is comparatively more efficient than C. striata and G. affinis. On the other hand C. striata and G. affinis had no significant difference in terms of their consumption. Hence, these species are more likely to have some larvae-eating capacity. Thus, the two native fish found capable of eating larvae and are comparable to the efficiency of established species, G. affinis -- Author's abstract.